Structural characterization of transfection nanosystems based on tricationic surfactants and short double stranded oligonucleotides - Andrzejewska, Weronika; Wilkowska, Michalina; Peplińska, Barbara; Skrzypczak, Andrzej; Kozak, Maciej (Biochemical and biophysical research communications, 2019)
For several years cationic surfactants have been the subjects of extensive studies as potential transgene carriers to be used in gene therapy. We report the formation of stable complexes between 21 base pairs oligonucleotides – siRNA, enhancing DMPK gene, and dsDNA and two tricationic surfactants (1,2,3-propanetri[oxymethyl-3-(1-dodecylimidazolium)]chloride and 1,2,3-propanetri[(oxymethyl)dimethyldodecylammonium]chloride. Structural studies by SAXS and TEM have shown that the dominant structure of the obtained lipoplexes is based on hexagonal, lamellar and cubic phases, packed in highly ordered aggregates. It has been established that tricationic surfactants can be used as siRNA carriers in gene therapy. •Tricationic surfactants form stable complexes with oligonucleotides (siRNA, dsDNA).•SAXS and TEM have shown the dominant structure of the obtained lipoplexes.•It was confirmed that tricationic surfactants can be used as siRNA carriers.